Non-Financial Dimensions of Family Firm Ownership: How Socioemotional Wealth and Familiness Influence Internationalization - Anne Sluhan (Copenhagen Business School (CBS), 2018)
This doctoral dissertation investigates idiosyncratic behaviors of family firms and contributes to an understanding of how family ownership affects the ways in which firms internationalize. While each chapter in the dissertation is a stand-alone work intended for publication, every study relates to an overarching research question about how non-financial dimensions of family firm ownership—exemplified by socioemotional wealth (SEW) and familiness—influence family firm internationalization. The dissertation contributes to varying literatures including family business, corporate governance, strategic management, and international business. Specifically, the review paper on family firm internationalization offers a novel presentation of entry modes along the FIBER dimensions of SEW. It proposes a framework to unbundle family firm-specific capabilities and motivations for internationalization for subsequent analysis utilizing the theoretical perspectives of SEW and familiness. The next chapter studies how family firm risk preferences affect behavior when engaging in cross-border acquisitions. While most studies on family firms implicitly assume businesses are run at the will of a controlling family, this paper abandons this assumption and examines whether (and how) non-family shareholders interact with family shareholders when deciding to internationalize. Results indicate international acquisitions will be of greater value when the level of family ownership is high or low, whereas the value of an acquisition is lower when family ownership is relatively balanced vis à vis non-family ownership. The final empirical chapter studies family firm behavior differently by exploring the notion of familiness within the context of an international acquisition. This study applies an action research methodology first to investigate how employees understand the notion of familiness and then to observe how this perception is actively mobilized to facilitate post acquisition integration. The paper emphasizes how aspects of familiness can be purposefully mobilized to facilitate integration, thus contributing to an understanding of familiness in general, and specifically familiness in a context of internationalization. From a methodological perspective, the paper contributes rich data showing how action research can be used in a business setting, presenting a process that facilitates integration between two distinct organizational and national cultures and between family and nonfamily firms as they face challenges in a post-merger or post-acquisition context.
hdl:10398/9626
Keywords: 650